Examining Power, GHG Emission and Financial Saving in Green Buildings: A Case Study of Jordan - Saidi, Abdul Ghafoor Ahmad; Shahateet, Mohammed Issa; Albaali, Ghani; Tweissi, Adiy; Sumadi, Mohammad (International Journal of Energy Economics and Policy, 2021)
The purpose of this research is to explore the effect of reducing Green House Gas (GHG) emissions in a case study of green buildings in Jordan through the use of photovoltaic solar panels to generate electricity. It also examines the use of photovoltaic solar cells to generate electricity and supplement Jordan’s national grid. The emission analysis is used to determine the case framework and the project’s GHG emissions, which is the CO2 project. The study’s findings demonstrate that implementing photovoltaic (PV) plans is economically feasible for Jordan’s electricity production. The annual energy savings are estimated to be 9315.61 kWh, which equates to a savings of over 3200 USD per year on the electricity bill. This is in addition to the annual reduction of GHG emissions by 920.7 tCO2, indicating that the case study initiated a beneficial event. The study contributes to filling a gap in the existing literature on the energy savings and environmental benefits of green buildings, which is deficient in developing countries due to a lack of applied research. The findings are not unique to Jordan; they could easily be applied to other developing countries as well. Keywords: CO2 emission, Green building, GHG, PV, solar thermal collector JEL Classifications: Q40, Q43, Q48, Q56, Q57 DOI: https://doi.org/10.32479/ijeep.11434